Struggles of the past and present: the African American woman in Harriet Jacobs’s Incidents in the Life of a Slave Girl and Chimamanda Adichie’s Americanah - Khan, Sadia (BRAC University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Master of Arts in English, 2019.